PENGARUH DESAIN PRODUK, PROMOSI, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPATU NIKE ORIGINAL PADA PELANGGAN SPORT STATION SOLO - Ardi Ansah (Univeristas Islam Bandung, 2017)
ABSTRACK One way to achieve the company's goal is to find out what the needs and desires of consumers or target market and give the satisfaction expected more effectively and efficiently than competitors. This study aims to analyze the influence of Product Design, Promotion and Brand together and partially on the Purchase Decision Original Nike shoes in Sport Station Solo.The population in this study are all consumers Sport Station in Solo. In this study, samples were taken of 100 respondents. The sampling technique used is the method of random sampling or random. The data used are primary data and secondary data. Data collection techniques in this study using questionnaires and interviews. Technical analysis of the data in this study using classic assumption test, multiple regression analysis, and hypothesis testing.Results of research on the influence of product design, promotion and brand image to the purchasing decision of customers of Nike shoes in Sport Station Original Solo can be known based on the simultaneous hypothesis test known the results of F 12.241> F table 2.70, Value Sig. 0.000 <0.05 it means Ho rejected, based on the partial results of hypothesis testing by t-test at a variable product design is known that the tcount 2.457> 1.984 t table then Ho is rejected, based on the partial results of hypothesis testing by t-test at promotion variables known that the thitung 2.984> ttabel 1,984 hence Ho refused, based on the test results of partial hypothesis with t test on variables brand image known that the tcount 2,949> ttabel 1,984 hence Ho refused, and based on the regression calculation can be seen that the coefficient of determination (R ²) were obtained for R2 amounting to 0.254 or 25.4%.The suggestions for this research that the company should complete the Sport Station product design, improve the promotion and brand image of Nike shoes that consumers are more interested in making purchasing decisions in Solo. It is suggested to further researchers to conduct research development by looking for other factors that can influence the purchasing decision. Keywords: Product Design, Promotion, Brand Image, Purchase Decision